Islam and the political discourse of modernity - Salvatore, Armando (International politics of the Middle East series, 1999)
Introduction: A genealogical approach to "political Islam" and political modernity -- Order and discourse. Communicative systems and the specialized quest for order -- The power of discourse and the discourse of power -- Public communication and frameworks of communal reference -- The emergence of transcultural dynamics. The "West" and "Islam": opposing essentialisms in an imbalanced game -- The genesis and development of "Arab-Islamic" discourse -- The sociologization of the western construction of Islam -- The western making of "political Islam". The linear hermeneutics of Islam "as such" -- The crisis of Orientalism and the return of Islam -- From Islam to politics, or the reverse? -- Towards an Islamic political discourse of modernity?. The new politics of al-sahwa al-islamiyya -- Is Islam the solution? -- Social justice and cultural heritage (turath) -- Thinking Islam